RISK MANAGEMENT AT THE LEVEL OF ROMANIAN SMALL AND MEDIUM-SIZED AGRICULTURAL BUSINESS - A SYSTEMATIC LITERATURE REVIEW - Edith-Andreea BARDUCZ; Ionel-Mugurel JITEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The small and medium-sized enterprise (SME) sector plays a crucial role in the economic framework, both at the national and European levels. Small and medium-sized firms (SMEs) are widely regarded as the most risk-averse ventures. Agricultural enterprises are particularly vulnerable to risk due to their strong reliance on climatic conditions. The objective of this study is to present a comprehensive analysis of the existing body of literature about risk management in small and medium-sized firms operating within the agricultural sector in Romania. Through a comprehensive and methodical examination of the specialist literature, following PRISMA 2020 guidelines a total of 16 out of 168 distinct publications found in the databases were deemed relevant and subjected to analysis. The study identified primary categories of risks encountered by these SMEs, including social, economic, environmental, market, production, operational, policy, technological, labor, knowledge, demographic, and resource risks. Additionally, various risk management methods were identified, including accessing public EU subsidies, recruiting skilled workers, offering home delivery services, engaging in risk-sharing mechanisms, implementing crop rotation methods, investing in new technology, and diversifying business operations. The study also highlighted internal factors, such as limited financial and technical resources, resistance to change, and fragmented approaches to risk management, as well as external factors like technological proliferation, regulatory changes, and market dynamics. The lack of comprehensive research in this field suggests a need for further investigation. This study provides a foundation for future research in risk management for agricultural SMEs.